Creating a Security Assurance System Using IoT and ML Technologies - Sargsyan, Siranush; Hovakimyan, Anna; Antonyan, Sveta (Transactions on Engineering and Computing Sciences, 2023)
The work is dedicated to the development of security systems using the Internet of Things and Machine Learning technologies. The need for such systems use is associated with the increase in crimes, as well as with the increase in number of attacks on special areas. The authors of the article have created a security system that is located in a guarded area. The security system reacts in real-time and informs about the expected danger through a picture or video. The security device senses the movement of any object in the area through sensors, and the camera connected to the device captures the moving object. A Siamese neural network examines the image. If it is from the class of unwanted objects, the app sends it to the Telegram app of the guard of the monitored area. The authors used Raspberry Pi, various sensor components, and a Siamese neural network to create the security system. The system can be implemented in bank vaults, offices, and special-purpose buildings. We, being the professors of the university, attach more importance to the use of the created system on the premises of the educational institution.